The multifaceted power of biochar: A review on its role in pollution control, sustainable agriculture, and circular economy - Amreen Bano; Mohd Kashif Aziz; Bablu Prasad; Rajesh Ravi; Maulin P. Shah; Pollyanna Vanessa Dos Santos Lins; Lucas Meili; Kumar Suranjit Prasad (Environmental Chemistry and Ecotoxicology)
The key challenges of the 21st century include global warming, soil health management, wastewater treatment, and adopting sustainable green technologies. Biochar offers significant potential in addressing these issues, positioning itself as a vital tool in advancing sustainable development goals. Recent biochar research has expanded significantly beyond its traditional focus in agricultural and environmental sciences. These characteristics position biochar as an increasingly valuable material for improving soil health, enhancing agricultural productivity, and capturing atmospheric carbon dioxide, contributing to efforts to mitigate global warming. The “circular economy” concept is rapidly gaining attraction, driven by its central goal of waste elimination through meticulous planning. Recently, biochar has emerged as a significant contributor in the environmental community due to its versatility in reducing waste and enhancing the efficacy of the circular economy. This review delves into advancements in the production, modification, and treatment methods of biochar, as well as its elemental and nutrient composition. It highlights the advantages, challenges, and diverse applications of biochar while critically examining current challenges and research gaps in its potential to mitigate greenhouse gas emissions, enhance soil carbon sequestration, and improve wastewater treatment processes.The potential of biochar to reduce greenhouse gas emissions and sequester carbon in soils, along with its applications in wastewater treatment, are thoroughly covered in this article. The challenges it faces and its prospects are also discussed in detail. This review identifies the key issues that must be addressed for the sustainable utilization of biochar. It explores the development of a circular economy-based environmental management paradigm, leveraging waste conversion into biochar and its diverse applications across regions, thus effectively closing the loop and exemplifying a truly circular economy in action.